Method for improving hole extrusion strength of carbon fiber reinforced composite material
By removing the prepreg part in the carbon fiber reinforced composite material and filling the metal sheet for hot pressing and curing, the problem of insufficient extrusion strength of the carbon fiber reinforced composite material is solved, and the effect of significantly improving the extrusion strength of the hole is achieved.
Patent Information
- Application Number
- CN202411375960.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical connection strength of carbon fiber reinforced composite materials is low after opening the hole, resulting in insufficient extrusion strength of the hole and unable to effectively bear the mechanical connection load.
Partially remove the intermediate layer in the prepreg, form a void and fill the metal sheet, and perform hot pressing and curing to form a laminated prepreg that is inclusion in the metal sheet, and use the high shear strength of the metal sheet to increase the hole under the hole extrusion Extrusion strength.
The pore extrusion strength of carbon fiber reinforced composite materials is significantly improved, and the shear strength of the metal sheet is higher than that of the composite material, and it can still carry the load even if plastic deformation occurs, which improves the strength of mechanical connections.
Smart Images

Figure CN119158986A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber reinforced composite material processing, in particular to a method for improving the hole extrusion strength of a carbon fiber reinforced composite material. Background Art
[0002] CFRP (carbon fiber reinforced composite material) is made of multiple layers of prepreg stacked at a certain design angle. It has excellent specific strength and specific modulus, but in actual use, holes will be opened for mechanical connection of components.
[0003] Currently, most CFRP holes are prepreg bodies that bear the mechanical connection load, resulting in low mechanical connection strength (ie, low hole extrusion strength). Summary of the invention
[0004] The purpose of the present invention is to provide a method for improving the hole extrusion strength of carbon fiber reinforced composite materials. Compared with the traditional prepreg bearing the mechanical connection load, the present invention can significantly improve the hole extrusion strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for improving the hole extrusion strength of a carbon fiber reinforced composite material, comprising the following steps:
[0007] Partially removing a plurality of intermediate prepreg layers in the prepregs to be stacked, wherein the positions of the removed portions correspond to the positions of the target openings of the carbon fiber reinforced composite material, and the size of the removed portions is greater than the size of the openings;
[0008] Then, the prepreg layers are stacked according to the designed layup. During the stacking process, the gaps formed by the removed parts of the prepreg are filled with metal sheets to obtain a laminated prepreg mixed with metal sheets. The number of the metal sheets is equal to the number of the gaps, and the shape and size of the metal sheets are equal to the shape and size of the corresponding gaps.
[0009] The laminated prepreg containing the metal sheets is subjected to hot pressing and curing to obtain a carbon fiber reinforced composite material;
[0010] The carbon fiber reinforced composite material is opened with holes.
[0011] Preferably, in the designed ply, each intermediate layer prepreg to be partially removed is distributed in a completely continuous manner, in a partially continuous manner, or in a completely spaced manner.
[0012] Preferably, the thickness of each gap-filled metal sheet is independently 0.1 to 0.5 mm.
[0013] Preferably, the total thickness of the metal sheet is ≤ 50% of the total thickness of the laminated prepreg containing the metal sheet.
[0014] Preferably, before the filling with the metal sheet, the metal sheet is roughened, cleaned and dried.
[0015] Preferably, the roughening treatment includes sandpaper grinding and / or laser roughening.
[0016] Preferably, the metal sheet includes a titanium alloy sheet and / or a steel sheet.
[0017] Preferably, the titanium alloy sheet comprises a TC4 titanium alloy sheet.
[0018] Preferably, the removed portion is in the shape of a rectangle with a length and width of 330 mm×50 mm.
[0019] Preferably, the opening is a mechanical drill hole.
[0020] The present invention provides a method for improving the hole extrusion strength of a carbon fiber reinforced composite material, comprising the following steps: partially removing a plurality of intermediate layers of prepreg in a prepreg to be stacked, the position of the removed portion corresponds to the position of the target opening of the carbon fiber reinforced composite material, and the size of the removed portion is greater than the size of the opening; then stacking each layer of prepreg according to the designed layering, during the stacking process, the gap formed by the removed portion of the prepreg is filled with a metal sheet to obtain a laminated prepreg with metal sheets; the number of the metal sheets is equal to the number of gaps, and the shape and size of the metal sheets are equal to the shape and size of the corresponding gaps; hot pressing and curing the laminated prepreg with metal sheets to obtain a carbon fiber reinforced composite material; and opening the carbon fiber reinforced composite material. The present invention includes metal sheets in the prepreg, and then opens holes at the positions of the metal sheets. Under the hole extrusion load, the shear strength of the metal sheet is significantly higher than the shear strength of the composite material, and even if the metal sheet is plastically deformed, it can still bear the load. Therefore, compared with the traditional prepreg bearing the mechanical connection load, the present invention can significantly improve the extrusion strength of the hole. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the stacking sequence of prepregs;
[0022] Figure 2 This is a schematic diagram of the ply laying after removing part of the middle layer prepreg;
[0023] Figure 3 This is a schematic diagram of the ply after filling with TC4 titanium alloy sheets;
[0024] Figure 4 This is a physical picture of the hot-pressed connection area of the included metal sheet in Example 1;
[0025] Figure 5A physical picture of the transition from the connection area to the non-connection area of the hot-pressed metal sheet hole in Example 1;
[0026] Figure 6 This is a photo of the holes in the hot-pressed composite plate with metal sheets in Example 1;
[0027] Figure 7 The displacement load curves of the single nail double shear extrusion test of the carbon fiber reinforced composite material hole of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0028] The present invention provides a method for improving the hole extrusion strength of a carbon fiber reinforced composite material, comprising the following steps:
[0029] Partially removing a plurality of intermediate prepreg layers in the prepregs to be stacked, wherein the positions of the removed portions correspond to the positions of the target openings of the carbon fiber reinforced composite material, and the size of the removed portions is greater than the size of the openings;
[0030] Then, the prepreg layers are stacked according to the designed layup. During the stacking process, the gaps formed by the removed parts of the prepreg are filled with metal sheets to obtain a laminated prepreg mixed with metal sheets. The number of the metal sheets is equal to the number of the gaps, and the shape and size of the metal sheets are equal to the shape and size of the corresponding gaps.
[0031] The laminated prepreg containing the metal sheets is subjected to hot pressing and curing to obtain a carbon fiber reinforced composite material;
[0032] The carbon fiber reinforced composite material is opened with holes.
[0033] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.
[0034] The present invention partially removes a plurality of intermediate layers of prepreg materials in the prepreg materials to be stacked.
[0035] The present invention has no special requirements for the removal method, and any method that can achieve the removal effect can be used, such as scissor cutting or laser cutting.
[0036] The present invention preferably first stacks all the prepregs to be stacked according to the designed layering sequence and layering angle, and the upper and lower layers of the prepreg membranes (which are carried when leaving the factory) are not torn off at this time; then the prepreg layers to be removed at the opening position are divided into areas and partially removed, and the upper and lower layers of the prepreg membranes are not torn off at this time; finally, the partially removed prepregs are re-stacked according to the initially designed layering sequence for subsequent use.
[0037] In the present invention, the position of the removed portion corresponds to the position of the target opening of the carbon fiber reinforced composite material, and the size of the removed portion is greater than the size of the opening.
[0038] In the present invention, the shape of the removed portion is preferably a rectangle. In an embodiment of the present invention, the length and width of the removed portion are 330 mm×50 mm, and the opening diameter is 6 mm.
[0039] In the present invention, in the designed ply, the intermediate layers of prepreg that are partially removed can be all continuously distributed, partially continuously distributed, or all spaced distributed. For example, there are 24 layers of prepreg to be stacked, and 5 to 10 layers in the ply are partially removed, so they are all continuously distributed; the 5th to 8th layers and the 17th to 20th layers in the ply are partially removed, so they are partially continuously distributed; the 5th, 8th and 10th layers in the ply are partially removed, so they are all spaced distributed. The present invention does not specifically limit which layers are partially removed, as long as they are intermediate layers, and preferably the gap height formed after the ply is 0.1 to 0.5 mm.
[0040] In the present invention, the total thickness of the partially removed intermediate prepreg layers is preferably ≤ 50% of the total thickness of the prepreg to be stacked (corresponding to the total thickness of the metal sheet described below ≤ 50% of the total thickness of the laminated prepreg containing the metal sheet).
[0041] The present invention has no special requirements for the prepreg, and any prepreg known in the art can be used, specifically unidirectional or woven prepreg; in the embodiment of the present invention, the prepreg used is specifically USN 12500 Guangwei composite material, which is a unidirectional prepreg with a size of 330mm×330mm and a thickness of 0.125mm.
[0042] After the partial removal is completed, the present invention stacks up the prepreg layers according to the designed layering. During the stacking process, the gaps formed by the removed parts of the prepreg are filled with metal sheets to obtain a laminated prepreg intercalated with metal sheets.
[0043] In the present invention, the number of the metal sheets is equal to the number of the gaps, and the shape and size of the metal sheets are equal to the shape and size of the corresponding gaps.
[0044] In the present invention, the metal sheet preferably includes a titanium alloy sheet and / or a steel sheet; the titanium alloy sheet preferably includes a TC4 titanium alloy sheet.
[0045] Before the metal sheet is used for filling, the present invention preferably further comprises roughening, cleaning and drying the metal sheet. In the present invention, the roughening treatment preferably comprises sandpaper polishing and / or laser texturing. In an embodiment of the present invention, 120-mesh sandpaper is used for polishing. The present invention improves the bonding strength between the metal sheet and the prepreg by roughening treatment. In the present invention, the cleaning is preferably wiped with dust-free paper dipped in anhydrous ethanol; the drying is preferably air-dried.
[0046] In the present invention, the thickness of each gap-filling metal sheet is preferably independently 0.1 to 0.5 mm; the total thickness of the metal sheets is preferably ≤ 50% of the total thickness of the laminated prepreg containing the metal sheets.
[0047] During the stacking process, the present invention preferably tears off the upper and lower film layers of the prepreg.
[0048] The present invention has no special requirements for the stacking process, and the stacking process well known in the art can be used. Specifically, a suitable mold is selected according to the shape of the carbon fiber reinforced composite material (for example, it can be a flat part or a curved part), and the mold release wax is evenly applied in the mold. Then, the layers of prepreg to be stacked are stacked in the lower mold according to the designed stacking order and stacking angle, and are rolled and compacted with a pressure roller from time to time.
[0049] After obtaining the laminated prepreg containing metal sheets, the present invention performs hot pressing and curing on the laminated prepreg containing metal sheets to obtain a carbon fiber reinforced composite material.
[0050] In the present invention, preferably, rubber strips are placed around the laminated prepreg containing the metal sheets, and an upper mold coated with release wax is covered, and the entire mold is transferred to a hot press for hot pressing and curing.
[0051] The present invention has no special requirements for the conditions of the hot pressing curing, and the hot pressing curing conditions known in the art can be selected according to the type of prepreg. In an embodiment of the present invention, when the prepreg is USN 12500 Guangwei composite material, the hot pressing curing is: heating to 120°C at a rate of 1°C / min, keeping warm for 90 minutes, and then naturally cooling from 120°C to 70°C, and the hot pressing pressure is 0.3MPa from beginning to end.
[0052] After obtaining the carbon fiber reinforced composite material, the present invention performs pore opening on the carbon fiber reinforced composite material.
[0053] In the present invention, the opening is preferably mechanical drilling. The present invention has no special requirements for the mechanical drilling method, and the mechanical drilling method known in the art can be used. In the embodiment of the present invention, a hole with a diameter of 6 mm needs to be drilled in two steps. Specifically, a small hole is first made with a 3 mm diameter carbide twist drill, and then a 6 mm diameter carbide twist drill is used to drill to the final hole. The drilling parameters of the two steps are a rotation speed of 1300 rpm and a feed of 30 mm / min.
[0054] The present invention incorporates metal sheets into the prepreg and then makes holes at the positions of the metal sheets. The shear strength of the metal sheets under the hole extrusion load is significantly higher than the shear strength of the composite material. Even if the metal sheets undergo plastic deformation, they can still bear the load. Therefore, compared with traditional prepregs that bear mechanical connection loads, the present invention can significantly improve the extrusion strength of the holes.
[0055] The method for improving the hole extrusion strength of a carbon fiber reinforced composite material provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0056] Example 1
[0057] The prepreg layer is [45 / 0 / -45 / 90] 3S , stack 24 unidirectional prepregs in order (do not tear the upper and lower layers of the prepreg film, such as Figure 1 As shown), the prepreg used is USN 12500 Guangwei composite material, with a size of 330mm×330mm and a thickness of 0.125mm;
[0058] Then, the 5th to 8th layers and the 17th to 20th layers in the laminate are partially removed, with a size of 50mm×330mm. In this step, the upper and lower layers of the prepreg are not torn (such as Figure 2 shown);
[0059] Lay the layers in the designed way, and do not tear the upper and lower layers of prepreg;
[0060] The nominal thickness of the TC4 titanium alloy sheet is 0.5mm, with a tolerance of ±0.1mm. The length and width of the TC4 titanium alloy sheet are 330mm×50mm. Use sandpaper with a grit of 120 to fully polish the upper and lower surfaces of the TC4 titanium alloy sheet, polish it evenly in the horizontal and vertical directions, then wipe it clean with dust-free paper dipped in anhydrous ethanol, and completely dry it for use;
[0061] Lay up the prepreg according to the designed layer. First, evenly apply the release wax on the mold, and then lay it up. During the layup process, tear off the upper and lower layers of the prepreg film and fill it with TC4 titanium alloy sheets (such as Figure 3 As shown), roll it with a roller from time to time to compact it;
[0062] Place rubber strips around the mold, cover the mold, and put it into the hot press. The hot pressing curing process is divided into three stages. In the first stage, the temperature rises slowly at a rate of 1°C / min. When the temperature rises to 120°C, it enters the second stage and keeps warm for 90 minutes. Finally, it enters the third stage. The hot pressed material is naturally cooled from 120°C to 70°C. The hot pressing pressure is 0.3MPa from beginning to end. Figure 4 This is a physical picture of the hot-pressed mixed metal sheet connection area; Figure 5 This is a physical picture of the transition from the hot-pressed metal sheet hole connection area to the non-connection area. Figure 4 and Figure 5 It can be seen that the metal sheet and the resin have a good transition;
[0063] The hot-pressed composite material is placed on the workbench of the water jet cutting machine and cut according to the size defined by the ASTMD5961 standard. The cut test piece is placed on the machining center for drilling. For a hole with a diameter of 6 mm, drilling is required in two steps. The first step is to use a 3 mm diameter carbide twist drill to make a small hole, and then use a 6 mm diameter carbide twist drill to drill to the final hole. The drilling parameters of the two steps are a speed of 1300 rpm and a feed of 30 mm / min. The actual photo of the resulting opening is shown in the figure. Figure 6 shown.
[0064] Comparative Example 1
[0065] The TC4 titanium alloy sheet is not used, and the rest is the same as in Example 1.
[0066] According to ASTM D5961 standard, the hole extrusion strength of Example 1 and Comparative Example 1 was tested. The test results are shown in Figure 7 .Depend on Figure 7 It can be seen that the extrusion limit load of Example 1 (doped TC4 metal sheet) is 23823N, and the extrusion limit load of Comparative Example 1 (composite hole) is 16595N; TC4 titanium alloy sheets are used to partially replace prepreg near the composite holes to bear the mechanical connection load. Compared with ordinary drilled CFRP specimens with the same hole diameter, the hole extrusion strength containing TC4 titanium alloy sheets can be increased by more than 40%.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the hole extrusion strength of a carbon fiber reinforced composite material, characterized in that: The following steps are involved: Partially removing a plurality of intermediate prepreg layers in the prepregs to be stacked, wherein the positions of the removed portions correspond to the positions of the target openings of the carbon fiber reinforced composite material, and the size of the removed portions is greater than the size of the openings; Then, the prepreg layers are stacked according to the designed layup. During the stacking process, the gaps formed by the removed parts of the prepreg are filled with metal sheets to obtain a laminated prepreg mixed with metal sheets. The number of the metal sheets is equal to the number of the gaps, and the shape and size of the metal sheets are equal to the shape and size of the corresponding gaps. The laminated prepreg containing the metal sheets is subjected to hot pressing and curing to obtain a carbon fiber reinforced composite material; The carbon fiber reinforced composite material is opened with holes.
2. The method according to claim 1, characterized in that In the designed ply, each intermediate layer prepreg that is partially removed is distributed in a completely continuous manner, in a partially continuous manner, or in a completely spaced manner.
3. The method according to claim 1, characterized in that The thickness of the metal sheet filling each gap is independently 0.1 to 0.5 mm.
4. The method according to any one of claims 1 to 3, characterized in that: The total thickness of the metal sheet is ≤ 50% of the total thickness of the laminated prepreg containing the metal sheet.
5. The method according to claim 1, characterized in that Before the metal sheet is used for filling, the metal sheet is roughened, cleaned and dried.
6. The method according to claim 5, characterized in that The roughening process includes sandpaper grinding and / or laser roughening.
7. The method according to any one of claims 1, 3 and 5 to 6, characterized in that: The metal sheet includes a titanium alloy sheet and / or a steel sheet.
8. The method according to claim 7, characterized in that The titanium alloy sheet comprises a TC4 titanium alloy sheet.
9. The method according to claim 1, characterized in that: The removed portion is in the shape of a rectangle, with a length and width of 330 mm×50 mm.
10. The method according to claim 1, characterized in that The opening is a mechanical drill hole.
Citation Information
Patent Citations
Method for improving interfacial property of titanium / fiber reinforced composite material laminate and composite material
CN107379725A
Preparation method of layering defect in composite material
CN112248482A
Preparation method of reference block for composite material processing layering defect detection
CN114755087A
Reinforcement thermoplastic-based fibre-metal laminate composite frame and manufacturing method thereof
EP4238758A1
Forming Method Of Composite Material And Product Using The Same
KR102466802B1
